A autoria na interpretação de Libras para o Português: aspectos prosódicos e construção de sentidos na perspectiva verbo-visual - Santos, Ricardo Ferreira (2018)
The simultaneous interpretation (SI) modality of Libras (Brazilian Sign Language) to Portuguese has been wining space in several activities on the educational circle. The performance of the Translator and Interpreter of Libras/Portuguese (TILSP, in Portuguese), in this context, demands articulations of theoretic-practical nature in order that the speech in Libras can be comprehended by interlocutors that are not familiar with the language. Due to generic formation and to the lack of practice, some interpreters present difficulties and insecurities in mobilizing speeches in communicative interactions. Therefore, the goal of this research is to analyze the authorship and construction of meaning in the speech-visual, through expressive intonation present in SI of Libras/Portuguese on the academic circle: conference genre. The intonation, prosodic element, is present on the Production and perception of each word or statement, in the oral speech or sign language. For this reason, our research questions are: (i) how the non-hand markers, in the Libras speech, can influence the prosody on Portuguese, specifically intonation; (ii) how the interpreter constructs meaning in SI through intonation; (iii) how is constituted the authorship in the intonation-discursive mobilization between Libras and Portuguese from the speech-visual perspective. By theory grounded in a dialogic perspective set in the Bakhtin Circle, the speech-visuality studies of Beth Brait, here understood as several materialization in the shape of texts in a visual and speech dimension constitutive in the production and construction of meaning, and the Interactional Intonation Theory (IIT) of David Brazil. From these, we made a methodological slide from the statements of verbal signs in sign language and from the materialization of speech-visual intonational signs through the complex enunciative-discursive mobilization fulfilled on the interpretation from Libras to Portuguese in conferences. We chose as corpus two SI of Libras to the oral modality (Portuguese) performed by TILSP at the II Event-Libras: matches and mismatches – at the Federal University of São Paulo (Unifesp, in Portuguese), campus Guarulhos. The analyses show that the interpreters on the SI activity, in a dialogical agitated environment, filled with the social vocal tensions, crossed through political speeches, controversial and ironic tones, perform or present some difficulties at the construction of meaning through the active comprehension and by the speech, visual and axiological position, materialized in the prosodic choices, constituting authorship in the interpretation. It is hoped that this research helps with the investigations of prosody and meaning construction between the modalities Libras/Portuguese, with the proposition of contributing with the formation of Libras interpreters and the work activities of these professionals